Implementation of Urban Agriculture Plan (green garden) in Razi University of Kermanshah and its Effects on Sustainable Development - Hadi Ebadi; Zahra Mohebi (Journal of Sustainability Perspectives, 2022)
Urban agriculture with the aim of completing urban food needs, providing ecosystem and environmental services, has multidimensional effects in any society in increasing cultural and social values and even increasing economic resilience.  The present study was conducted on the implementation of urban agriculture plan (green garden) in Razi University of Kermanshah and investigated the effects of urban agriculture on sustainable development. Therefore, it will provide the conditions for strengthening social interaction and economical and environmental. as well as will pave the way for culture-building commensurate with the development of urban agriculture and the results obtained from it can be used in the process of planning and macro-agricultural policies in the different places.Keyword: green spaces, pandemic, social relationships, Covid-19